Of caves and shell mounds - Carstens, Kenneth Charles; Watson, Patty Jo, 1932- (Book collections on Project MUSE., 1996)
Ancient human groups in the Eastern Woodlands of North America were long viewed as homogeneous and stable hunter-gatherers, changing little until the late prehistoric period when Mesoamerican influences were thought to have stimulated important economic and social developments. The authors in this volume offer new, contrary evidence to dispute this earlier assumption, and their studies demonstrate the vigor and complexity of prehistoric peoples in the North American Midwest and Midsouth. These peoples gathered at favored places along midcontinental streams to harvest mussels and other wild fo.